(3GNJUGQ QaY GdMLGH Yf eNHBJ GdTgGHs - (3ESeGYjd Hf eMeO Hf ESeGYjd GdMVQeis; (3GHf MHjH GdHZOGOj GdbVGYjs
(3ChdgG (B:s
(3hHYO aEf GdTjN CHGHcQ eMeO Hf Ydi GdYGeQi GdHZOGOj GdhGYX TQM cJGH GdTgGH GdPi Ufag GdEeGei GdbVGYi s
(3BNQgG (B:s
(3Cba Ydjg hdGMQL acGf eYXe GdebUhO TQM eJhf GdCMGOjK hGdCdaGX hGfJgi cdGe GdTGQM s
(3GdfSNI HgG MhGTs
(3hQaY GdfbGH Yf cJGH GdTgGH ddbVGYi gh TQM dcJGH TgGH GdCNHGQ ai GdMce hGdCeKGd hGdBOGHs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdMOjK h GdeUWdMs